Need legit answer with steps genuine will get brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d02/ea2050c690cb627b1445bd0854803fcb.jpg)
Answers
Answered by
9
Answer:
Let,
L=limx→0(1−4x)1−xx
=limx→0(1−4x)1x−1
=limx→0(1−4x)1x(1−4x)−1
limx→0(1−ax)bx=eab
limx→0(1−4x)−1=1
So,
L=e−4
Step-by-step explanation:
Hope it helps!
Answered by
4
Step-by-step explanation:
i have attached the photos...hope it may help
Attachments:
![](https://hi-static.z-dn.net/files/dd1/3a5d17bdb14f513cdd03d677332287d2.jpg)
![](https://hi-static.z-dn.net/files/d01/2bf038facddce185adedfa6bfae4a214.jpg)
Similar questions